Increased circulating Endothelin-1 is a risk factor for ECMO use and mortality in neonates with congenital diaphragmatic hernia: a prospective observational study - Lemloh, Lotte; de Vadder, Aster; Melaku, Tamene; Bo, Bartolomeo; Patel, Neil; Holdenrieder, Stefan; Müller, Andreas; Kipfmüller, Florian (Respiratory research, 2025)
Elevated levels of Endothelin-1 (ET-1), a vasoactive peptide, have been associated with adverse outcomes in neonates with congenital diaphragmatic hernia (CDH). However, the relationship between ET-1 levels and clinical outcomes remains poorly understood. This study aimed to investigate the kinetics of ET-1 levels in CDH neonates from birth to 48 h postnatally and assess its association with clinical comorbidities, the need for extracorporeal membrane oxygenation (ECMO), and mortality.